Review of Land Ownership Certificate Dispute Settlement Based on Kupang PTUN Decision Number 42/G/2023/PTUN.KPG - Suryani, Cendana; Hartono, Margareta Kristiani; Rasji, Rasji (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Agricultural issues are complex and sensitive problems that affect many aspects of life, including social, economic, political, and psychological aspects. Land disputes are a recurring and relevant topic. Obtaining land as a capital for various needs along with population growth, development trends, and access to various parties. Ways to resolve land disputes can be done through mediation, arbitration, or litigation. Mediation is the preferred method because it is a family matter and does not require a large cost. Arbitration is a method of resolving disputes outside the court with a neutral third party as an arbitrator. Litigation is a method of resolving disputes through the court, and it is the last resort. The research method used is through the use of primary data, namely mediation data and legal documents related to land disputes for a total of people. The Minister of Agriculture and Plantation Regulation No. 11 and the Director General of the National Land Agency in 2016 on Land Dispute Resolution states that land disputes can be resolved both within and outside the court.